The Role of Institutional Repositories in the Dissemination and Impact of Community-Based Research - Bradley, Cara (Evidence Based Library and Information Practice, 2021)
Objective – The goals of this study were to 1) characterize the quantity and nature of research outputs created by or in cooperation with community-based research units (CBRUs) at Canadian universities; 2) assess dissemination practices and patterns with respect to these outputs; 3) understand the current and potential roles of institutional repositories (IRs) in disseminating community-based research (CBR). Methods – The researcher consulted and consolidated online directories of Canadian universities to establish a list of 47 English language institutions. Working from this list of universities, the researcher investigated each in an attempt to identify any CBRUs within the institutions. Ultimately, these efforts resulted in a list of 25 CBRUs. All but 1 of these were from universities that also have IRs, so 24 CBRUs were included for further analysis. The researcher visited the website for each CBRU in February 2021 and, using the data on the site, created a list of each project that the CBRU has been involved in or facilitated over the past 10 years (2010-2020). An Excel spreadsheet was used to record variables relating to the nature and accessibility of outputs associated with each project. Results – These 24 CBRUs listed 525 distinct projects completed during the past 10 years (2010-2020). The number of projects listed on the CBRU sites varied widely from 2 to 124, with a median of 13. Outputs were most frequently reports (n=375, which included research reports, whitepapers, fact sheets, and others), with journal articles (n=74) and videos (n= 42) being less common, and other formats even less frequent. The dissemination avenues for these CBRU projects are roughly divided into thirds, with approximately one third of the projects’ results housed on the CBRU websites, another third in IRs, and a final third in “other” locations (third party websites, standalone project websites, or not available). Some output types, like videos and journal articles, were far less likely to be housed in IRs. There was a significantly higher deposit rate in faculty or department-based CBRUs, as opposed to standalone CBRUs. Conclusion – The results of this study indicate that academic libraries and their IRs play an important role in the dissemination of CBR outputs to the broader public. The findings also confirm that there is more work to be done; academic librarians, CBRU staff, and researchers can work together to expand access to, and potentially increase the impact of, CBR. Ideally, this would result in all CBRU project outputs being widely available, as well as providing more consistent access points to these bodies of work.